Uji Pertumbuhan Tanaman Pakcoy (Brassica rappa L) Dengan Pemberian Nutrisi Ab-Mix Dan Pupuk Organik Cair Pada System Hidroponik - Ria Megsari; Asmuliani R (Musamus Journal of Agrotechnology Research, 2020)
This research aimed to test the growth of pakcoy plants by providing AB-mix and POC nutrients in the hydroponic system. This research star from November 2019 to January 2020 in the Pohuwato University experimental garden. The experiment used a Factor Two Factor (F2F) experiment in a Randomized Block Design (RBD), The first factor is the use of AB-mix with three levels, AB-mix, AB-mix 1.2 ml/l, and AB-mix 1.8 ml/l. The second factor is the use of POC Nasa with two levels, namely POC Nasa 5 ml/l and POC Nasa 10 ml/l. So that there are 6 treatment combinations, where each treatment is repeated 3 times with a total unit experiment of 18 units. The results showed that the giving of AB-mix nutrition 1.2 ml/l, at the age of 6 MST gave the best growth height (5,944 cm) and number of leaves (15,750 strands) on pakcoy plants. Whereas the giving of POC Nasa at the age of 6 MST gave the best results in the treatment of 10 ml/l at plant height parameters (5.556 cm). However, there was no interaction between the treatment of AB-mix and POC Nasa for pakcoy plant growth. Keywords: Hydroponics, AB-mix, Pakcoy, POC